2008
DOI: 10.1111/j.1750-3841.2007.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sodium Chloride and Glucose on the Aggregation Behavior of Heat‐Denatured Ovalbumin Investigated with a Multiangle Laser Light Scattering Technique

Abstract: The molecular characteristics of ovalbumin aggregates formed by heating with NaCl and glucose were investigated with a multi-angle laser light scattering system. The presence of NaCl and glucose affected the formation and molecular structure of the aggregates. Specifically, glucose increased the denaturation temperature of ovalbumin due to thermal stabilization of the native state of ovalbumin, regardless of the content of added NaCl. The surface hydrophobicity of the aggregates was increased by the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…Bryant and McClements (1998) reported that the structure of protein aggregates could differ between those formed in the presence and absence of an electrolyte because of complete or partial screening of the electrostatic repulsion between the protein aggregates and the possibility of forming bonds between nonpolar groups due to attractive hydrophobic interaction. The weight‐averaged molar masses ( M w ) of ovalbumin aggregates prepared with 2, 5, and 10 mM NaCl were 2, 4, and 25 times greater than that without NaCl and 2, 3, and 5 times greater for the root mean square radius ( R g ), respectively (Choi and Moon 2007). In addition, the surface hydrophobicities (SHs) of ovalbumin aggregates prepared with 2, 5, and 10 mM NaCl were 1, 1.5, and 2 times greater than those without NaCl, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bryant and McClements (1998) reported that the structure of protein aggregates could differ between those formed in the presence and absence of an electrolyte because of complete or partial screening of the electrostatic repulsion between the protein aggregates and the possibility of forming bonds between nonpolar groups due to attractive hydrophobic interaction. The weight‐averaged molar masses ( M w ) of ovalbumin aggregates prepared with 2, 5, and 10 mM NaCl were 2, 4, and 25 times greater than that without NaCl and 2, 3, and 5 times greater for the root mean square radius ( R g ), respectively (Choi and Moon 2007). In addition, the surface hydrophobicities (SHs) of ovalbumin aggregates prepared with 2, 5, and 10 mM NaCl were 1, 1.5, and 2 times greater than those without NaCl, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The M w , R g , and SH of ovalbumin aggregates that contained different NaCl concentrations were different from those of aggregates without NaCl. The M w of soluble aggregates that contained 0, 2, 5, and 10 mM NaCl were 1.86, 2.74, 6.83, and 34.90 × 10 6 g/mol, respectively, and the R g for soluble aggregates that contained 0, 2, 5, and 10 mM NaCl were 14.8, 25.4, 44.3, and 80.4, respectively (Choi and Moon 2007). In addition, the SHs of ovalbumin aggregates that contained 0, 2, 5, and 10 mM NaCl were 653, 684, 901, and 1465, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The egg white sample had two endothermic peaks. From published literature [2,9], the first peak corresponded to ovotransferrin and the second peak corresponded to ovalbumin. Several factors, such as pH and the presence of salt or sucrose, are known to af fect denaturation temperatures [14].…”
Section: Theory Of Kinetics Of Thermal Protein Denaturationmentioning
confidence: 99%
“…Several studies have focused on changes in the physicochemical properties of egg constituents during heat treatment and these can be classified into two groups. One is the identification of the denaturation temperature of egg proteins, which are the major components of the egg, using differential scanning calorimetr y (DSC) [2][3][4][5][6][7][8][9]. The other focuses on the study of fluctuations of the gel-point temperature and rheological properties using dynamic viscoelastic oscillatory measurements [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation